MDCT Detection of Omental Metastases with Peritoneal Carcinomatosis and Ascites in Prostate Cancer: An unusual metastatic site - Rekha, Khaleda Parvin; Ray, Deepak Shankar; Jubaida, Razina; Sharif, Md Mofazzal; Hussain, Musharraf (KYAMC Journal, 2022)
Prostate cancer is the second most common cause of cancer related death in males. The most common sites of prostate cancer metastases include bone and regional lymph nodes followed by lung, liver and brain. Peritoneal metastasis without skeletal involvement is extremely rare, with only a few cases reported in the literature. We present herein a patient of prostate cancer with omental metastases and peritoneal carcinomatosis accompanied by ascites but without bone metastases. The importance of this case report is to keep in mind that the lack of skeletal involvement does not exclude the possibility of distant metastases in prostate cancer. Prostate cancer can present with distant metastases in unexpected sites. The presence of ascites may indicate peritoneal involvement. KYAMC Journal Vol. 13, No. 02, July 2022: 124-126